Ecological Discourse Analysis based on Theme System: Taking Xi Jinping’s Important Speeches at the Belt and Road Forum for International Cooperation as an Example - Wang, Youqing; Zhang, Dan (International Journal of Social Sciences and Public Administration, 2025)
Based on the textual function of Systemic Functional Linguistics, this study employs the theme system to conduct an ecological discourse analysis of Xi Jinping’s important speeches at the Belt and Road Forum for International Cooperation. The aim is to explore the ecological sense of the selected text and further validate the practical value of He and Ma’s extension of the theme system in ecological discourse analysis from the perspective of ecolinguistics. The findings reveal that the markedness of participant role themes effectively highlights the ecological attributes of clauses. In the discourse, participant roles of social factors often serve as themes, with various ecological factors alternating, reflecting the diversity and interactivity of these roles. This underscores the broad participation and cooperation across the globe under the Belt and Road Initiative, further illustrating China’s steadfast commitment and contributions to advancing high-quality Belt and Road cooperation. Consequently, the discourse demonstrates a strong ecological orientation and is therefore regarded as ecologically beneficial.